2011
DOI: 10.1021/jp202441x
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects in Cation−π Interactions: A Unified View from Inductive, Resonance, and Through-Space Effects

Abstract: The quantification of inductive (I), resonance (R), and through-space (TS) effects of a variety of substituents (X) in cation-π interactions of the type C₆H₅X···Na⁺ is achieved by modeling C₆H₅-(Φ₁)(n)-X···Na⁺ (1), C₆H₅-(Φ₂)(n)-X···Na⁺ (2), C₆H₅-(Φ(2perpendicular))(n)-X···Na⁺ (2'), and C₆H₆ ···HX···Na⁺ (3), where Φ₁ = -CH₂CH₂-, Φ₂ = -CHCH-, Φ(2perpendicular) indicates that Φ₂ is perpendicular to the plane of C₆H₅, and n = 1-5. The cation-π interaction energies of 1, 2, 2', and 3, relative to X = H and fitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 24 publications
1
61
0
Order By: Relevance
“…1,4,9,15,28−32 For instance, in the case of C 6 H 5 X···Na + systems, compared to X = H, electron-donating (ED) substituents show stronger cation−π binding whereas electron-withdrawing (EW) substituents show weaker cation−π binding. [22][23][24]33 Recently, we have shown that the total substituent effect experienced by the C 6 H 5 X···Na + system is equal to the sum of the contributions of inductive, resonance and through-space effects of X. 22 Further, in a series of studies we have shown that molecular electrostatic potential (MESP) topographical analysis provides accurate quantification of substituent effect in organic and inorganic systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,4,9,15,28−32 For instance, in the case of C 6 H 5 X···Na + systems, compared to X = H, electron-donating (ED) substituents show stronger cation−π binding whereas electron-withdrawing (EW) substituents show weaker cation−π binding. [22][23][24]33 Recently, we have shown that the total substituent effect experienced by the C 6 H 5 X···Na + system is equal to the sum of the contributions of inductive, resonance and through-space effects of X. 22 Further, in a series of studies we have shown that molecular electrostatic potential (MESP) topographical analysis provides accurate quantification of substituent effect in organic and inorganic systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More recently, Sayyed and Suresh [75] attempted to separate induction, resonance, and through-space (field) effects of substituted arenes in cation/p interactions. In their model, the substituents are linked to the benzene ring by a variety of spacers, and interaction energies were derived using an extrapolation procedure.…”
mentioning
confidence: 99%
“…In their model, the substituents are linked to the benzene ring by a variety of spacers, and interaction energies were derived using an extrapolation procedure. Sayyed and Suresh concluded [75] that in cation/p interactions, electron-withdrawing groups mainly operate via through-space effects, whereas the effects of electron donating substituents are transmitted through p resonance effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of studies from our laboratory, we have established that EPN is a remarkably accurate descriptor of the abilities of specific atomic centers in molecules to form hydrogen bonds [42][43][44][45][46][47] and also in quantifying chemical reactivity [48][49][50][51]. In later years, EPN values have been successfully employed by other authors in examining reactivity trends [52][53][54][55][56][57][58][59][60]. Politzer and Thruhlar [61] defined the electrostatic potential at nuclei Y (V Y ) by Eqn.…”
Section: Computational Mehtodsmentioning
confidence: 99%